SISTEM PENDUKUNG KEPUTUSAN PENENTUAN SALES TERBAIK DI PT MGM MENGGUNAKAN METODE WASPAS - Jaya, Jessica Thalia; Kesuma, Dorie P. (JATISI, 2025)
PT MGM, an automotive company, currently conducts periodic assessments to determine its best salespersons. This process, however, is performed manually using Microsoft Excel. This process is inefficient, time-consuming, subjective, and lacks transparency for the sales staff being assessed. This research aims to design a decision support system (DSS) to overcome this problem. This system was developed using the Waterfall method, utilizing the PHP programming language and MySQL database for its application development. The Weighted Aggregated Sum Product Assessment (WASPAS) method is used to calculate and rank the best salespersons based on established criteria, such as sales volume, attendance, and performance evaluation. The result of this research is a web-based DSS application capable of managing sales assessment data. Based on user satisfaction testing via questionnaires administered to HRD, ADH, Directors, and Sales staff, the system received a positive response as it functions properly and simplifies the assessment and performance monitoring process. The implementation of this system significantly improves the objectivity, effectiveness, and speed of the assessment process, while also reducing the risk of input errors. This system also provides transparency as sales staff can view their own performance results.